Stem cell proteomes: a profile of human mesenchymal stem cells derived from umbilical cord blood - Feldmann, Robert Enrico; Bieback, Karen; Maurer, Martin H.; Kalenka, Armin; Bürgers, Heinrich; Groß, Benjamin; Hunzinger, Christian; Klüter, Harald; Kuschinsky, Wolfgang; Eichler, Hermann (Electrophoresis, 2005)
Multipotent mesenchymal stem cells (MSCs) derived from human umbilical cord blood (UCB) represent promising candidates for the development of future strategies in cellular therapy. To create a comprehensive protein expression profile for UCB-MSCs, one UCB unit from a full-term delivery was isolated from the unborn placenta, transferred into culture, and their whole-cell protein fraction was subjected to two-dimensional electrophoresis (2-DE). Unambiguous protein identification was achieved with peptide mass fingerprinting matrix-assisted laser desorption/ionization - time of flight - mass spectrometry (MALDI-TOF-MS), peptide sequencing (MALDI LIFT-TOF/TOF MS), as well as gel-matching with previously identified databases. In overall five replicate 2-DE runs, a total of 2037 ± 437 protein spots were detected of which 205 were identified representing 145 different proteins and 60 isoforms or post-translational modifications. The identified proteins could be grouped into several functional categories, such as metabolism, folding, cytoskeleton, transcription, signal transduction, protein degradation, detoxification, vesicle/protein transport, cell cycle regulation, apoptosis, and calcium homeostasis. The acquired proteome map of nondifferentiated UCB-MSCs is a useful inventory which facilitates the identification of the normal proteomic pattern as well as its changes due to activated or suppressed pathways of cytosolic signal transduction which occur during proliferation, differentiation, or other experimental conditions.
Gesehen am 30.04.2021